Potential of Malang Robusta Coffee Beans as Anti-breast Cancer In-Vitro - Utami, Novi Fajar; Elya, Berna; Hayun, Hayun; Kusmardi, Kusmardi; Nur, Syamsu; Fajriati, Annisa (Universitas Pakuan, 2023)
Robusta coffee from Malang Regency, East Java is one of the superior products of the largest coffee-producing region in Indonesia. The coffee has high antioxidants. The component that acts as an antioxidant is the tannin content, and these tannins are also anti-cancer. Using the UV-Vis spectrophotometry method the tannin content in Malang Robusta coffee beans is known and then to measure its ability as an anticancer in-vitro against breast cancer cells using MCF-7. The results showed that the tannin contained in Malang Robusta coffee bean extract was 2.81 % and inhibited MCF-7 at 400 µg/mL, it has potential as an anticancer with an inhibition value of 68.88 %. Therefore, the use of Robusta coffee from Malang at this concentration can be used as an anti-breast cancer agent.